Developing a toolkit to assist in the decision-making process of LSPs to shift to the use of bimodal transport in South Africa - Van der Merwe, Daniel (Stellenbosch : Stellenbosch University, 2021)
Thesis (MEng)--Stellenbosch University, 2021.